The Regulation and Function of Fibroblast Growth Factor 8 and Its Function during Gonadotropin-Releasing Hormone Neuron Development - Chung, Wilson C. J.; Linscott, Megan L.; Rodriguez, Karla M.; Stewart, Courtney E. (Frontiers in Endocrinology, 2016)
Over the last few years, numerous studies solidified the hypothesis that fibroblast growth factor (FGF) signaling regulates neuroendocrine progenitor cell proliferation, fate-specification, and cell survival, and therefore is critical for the regulation and maintenance of homeostasis of the body. One important example that underscores the involvement of FGF signaling during neuroendocrine cell development is gonadotropin-releasing hormone (GnRH) neuron ontogenesis. Indeed, transgenic mice with reduced olfactory placode (OP) Fgf8 expression do not have GnRH neurons. This observation indicates the requirement of FGF8 signaling for the emergence of the gonadotropin-releasing hormone (GnRH) neuronal system in the embryonic OP, the putative birth place of GnRH neurons. Mammalian reproductive success depends on the presence of GnRH neurons to stimulate gonadotropin secretion from the anterior pituitary, which activates gonadal steroidogenesis and gametogenesis. Together, these observations are critical for understanding the function of GnRH neurons and their control of the hypothalamus-pituitary-gonadal (HPG) axis to maintain fertility. Taken together, these studies illustrate that GnRH neuron emergence, and hence HPG-function is vulnerable to genomic and molecular signals that abnormally modify Fgf8 expression in the developing mouse OP. In this short review, we focus on research that is aimed at unraveling how androgen, all-trans retinoic acid and epigenetic modifies control mouse OP Fgf8 transcription in the context of GnRH neuronal development, and mammalian reproductive success.